Rubberwood Utilization Seminar: proceedings - Rubberwood Utilization Seminar (2nd : 1985 : Kuala Lumpur); Daljeet Singh, K.; Choo, Kheng Ten; Hong, Lay Thong; Institut Penyelidikan Perhutanan Malaysia (Kuala Lumpur : Forest Research Institute Malaysia, 1987)
28